Water–soluble extracts from banana pseudo–stem as functional additives for polylactic acid: Thermal and mechanical investigations. (March 2019) - Sango, Thomas; Stoclet, Gregory; Joly, Nicolas; Marin, Adeline; Cheumani Yona, Arnaud M.; Duchatel, Lucie; Kor Ndikontar, Maurice; Lefebvre, Jean–Marc
Graphical abstract: Highlights: Extraction and characterization of water soluble extracts (WSE) of the banana pseudo-stem are described. PLA materials filled with WSE are casted with various WSE amounts. Mechanical and thermal properties of PLA/WSE materials are determined. Nucleating and slight plasticizing effects of WSE on PLA crystallization and plasticization behaviours are revealed. Abstract: Water–Soluble Extracts (WSE) were obtained from Banana Pseudo–stems (BPS) using a simple and robust deconstruction procedure. WSE were characterized by FTIR, WAXS, TGA–DTG analysis. With the objective of developing fully bio–based polymer formulations, WSE fillers were blended to Poly Lactic Acid (PLA) using a solution blending, casting and thermocompression process. Thermal and mechanical properties were investigated by Differential Scanning Calorimetry (DSC), Dynamic Mechanical Analysis (DMA) and uniaxial tensile tests on neat–PLA (n–PLA) and PLA/WSE blends at various filler contents. Thermal DSC investigations established that WSE act as a plasticizer on PLA. This was further confirmed by DMA by the shift of the loss factor (tan δ) peak maximum towards lower temperatures. WSE also significantly impacted the thermally induced crystallization of PLA and the nucleating power of WSE was assessed by isothermal and non–isothermal studies. WSE had a detrimental effect on PLA brittleness and a slightly positive influence on its stiffness in the glassy state, whereas the drawability remained fairly acceptable when PLA–based materials where drawn at 75 °C above Tg . Moreover, WSE induced an earlier strain–hardening of the composite films as compared to neat PLA. These results underline the valorization potential of such agricultural by–products for sustainable polymer applications in the packaging industry.